HUBUNGAN TINGKAT PENGETAHUAN DAN LINGKUNGAN SOSIAL DENGAN PERILAKU MEROKOK - Ariasti, Dinar; Ningsih, Endang Dwi (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2020)
Background. Smoking can cause health problems. Riskesdas in 2018 showed that the prevalence of smoking in adolescents aged 10-18 years has increased from 2013 (7.20%) to 2018 (9.10%) so that it is still very far from the RPJMN of 2019 was 5.4%.The Aim of the Study. To determine the relationship of the level of knowledge and social environmental factors with smoking behavior of students of SMA Negeri 8 Surakarta.Subjects and Methods. This research is an observational analytic with correlational design. Subjects were male students who smoked in SMA Negeri 8, samples were taken based on the Kretjie table, data were analyzed with the Spearman Rank Correlation test.Results. There is a relationship between the level of knowledge (p = 0.001; r = -0.591) and the family environment (p = 0.028; r = 0.272) but there is no relationship between the school environment (p = 0.105) and the community environment (p = 0.056) with smoking behavior. Conclusion. There is a relationship between the level of knowledge and family environment with smoking behavior but there is no relationship between the school environment and the community environment with smoking behavior.Keywords: knowledge, smoking behavior, social environment.Korespondensi: Dinar Ariasti. AKPER PANTI KOSALA SURAKARTA, Jalan Raya Solo-Baki Km. 4 Gedangan, Grogol, Sukoharjo, Jawa Tengah. Email: ariasti98@gmail.com